2002
DOI: 10.1124/mol.61.2.285
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Kv1.5 Currents by Protein Kinase A, Tyrosine Kinase, and Protein Tyrosine Phosphatase Requires an Intact Cytoskeleton

Abstract: The regulation of cardiac delayed rectifier potassium (Kv) currents by cAMP-dependent protein kinase (PKA) contributes to the control of blood pressure and heart rate. We investigated the modulation by PKA and protein phosphatases of cloned Kv1.5 channels expressed in Xenopus laevis oocytes. Exposure of oocytes to activators of PKA (100 nM forskolin, 1 mM 8-bromo-cAMP, or 1 mM 3-isobutyl-1-methylxanthine) had no effect on the amplitude of Kv1.5 currents. Inhibition of PKA by injection of protein kinase A inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 39 publications
0
42
0
Order By: Relevance
“…It has been established that this type of regulation involves the production of cAMP and subsequent phosphorylation by protein kinase A (PKA). Tyrosine kinases have also been reported to modulate the activity of cardiac ion channels (Shuba & McDonald, 1997;Zhou et al, 1997;Wang & Lipsius, 1998;Hool et al, 1998;Maier et al, 1999;Mason et al, 2002;Tiran et al, 2003). We previously demonstrated that genistein, a tyrosine kinase inhibitor, can increase the sensitivity of cardiac ion channels to b 1 -AR stimulation, suggesting that basal tyrosine kinase activity inhibits badrenergic responsiveness in cardiac myocytes (Hool et al, 1998).…”
Section: Introductionmentioning
confidence: 98%
“…It has been established that this type of regulation involves the production of cAMP and subsequent phosphorylation by protein kinase A (PKA). Tyrosine kinases have also been reported to modulate the activity of cardiac ion channels (Shuba & McDonald, 1997;Zhou et al, 1997;Wang & Lipsius, 1998;Hool et al, 1998;Maier et al, 1999;Mason et al, 2002;Tiran et al, 2003). We previously demonstrated that genistein, a tyrosine kinase inhibitor, can increase the sensitivity of cardiac ion channels to b 1 -AR stimulation, suggesting that basal tyrosine kinase activity inhibits badrenergic responsiveness in cardiac myocytes (Hool et al, 1998).…”
Section: Introductionmentioning
confidence: 98%
“…A myriad of studies over the past 40 years have identified hundreds (if not thousands) of PKA substrates, both in the nucleus and in the cytoplasm (Budovskaya et al 2005, Huang et al 2007, Neuberger et al 2007, Gao et al 2008. Like other post-translational protein modifications, PKAmediated phosphorylation can affect any aspect of target protein function, including activity, localization, and stability (Huang et al 2000, Mason et al 2002, Higuchi et al 2003, Qiao et al 2003, Hoang et al 2004, Hino et al 2005, Rolli-Derkinderen et al 2005, such that PKA exerts complex effects on most biologic systems. For this reason, pharmacologic or genetic manipulation in tissue culture cells may produce only a limited understanding of the pleomorphic role of PKA signaling.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac Kv1.5 channels also couple to the actin cytoskeleton, which regulates current density and channel localization (20). Recently, it has been shown that modulation of Kv1.5 currents by protein kinase A requires an intact cytoskeleton (21). Specific disruptors for cytoskeletons have been used in analyzing the functional roles of the cytoskeleton, including modulation of ion channel activities.…”
Section: Discussionmentioning
confidence: 99%
“…There are several previous reports (20,21,33,37) showing the regulation of ion channels by cytoskeleton. Maruoka et al (20) have reported that disruption of the actin cytoskeleton with cytochalasin B or cytochalasin D significantly increases Kv1.5-dependent K ϩ currents in Kv1.5-expressing human embryonic kidney cells.…”
Section: Discussionmentioning
confidence: 99%